Career Guidance for the Hospitality Industry during the Pandemic for Students of SMKN 7 Tangerang - Oqke Prawira; Adestya Ayu Armielia; Rangga Anggara (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
During the pandemic, the continuity of job opportunities related to the tourism industry was concerning for vocational high school students, including students at SMKN 7 Kabupaten Tangerang. Therefore, socialization of career guidance regarding the hospitality industry during a pandemic is necessary so that students can anticipate their career plans after the study period is over. This community outreach activity is carried out so that students can have an understanding of their own potential and development in related industries and plan for the future according to their potential and interests rationally according to existing job opportunities. The material presented is related to the condition of the hospitality industry during Covid-19 pandemic and how to respond to this. The method applied to this community outreach was Service Learning Method as the activities were actively applying what was learnt in the campus to the community. The community outreach activities consist of 3 stages, namely the preparation, implementation, and evaluation stages. Activities are carried out online as a security measure during pandemic. After the activity ends, students can explore career development, identify their potential interests and talents, add relevant information to make career decisions, and improve their expertise and skills according to the career map made.